Superconductors and superconductivity - Kolisnychenko, Stanislav (Specialized collections, 2015)
Application of superconducting material in measuring devices, medical diagnostics, in space and energy industries and transport, is only a short list of possible use of the phenomenon of superconductivity in everyday human activity.